UI/UX Design Analysis and Design Using The Design Thinking Method On PT. Ridho Makmur Sentosa Website - Purnamasari, Indah; Wicaksono Putra, Aldhan (Journal of Computer Science and Informatics Engineering, 2026)
The development of information technology demands that companies provide efficient and easy-to-use digital services. PT. Ridho Makmur Sentosa, as a logistics service provider, faces obstacles in delivering shipping information through a website whose interface is less than optimal and does not support the user experience. This study aims to analyze and redesign the UI/UX appearance of the Ridho Logistics website using a Design Thinking approach that focuses on user needs. This method is implemented through five stages, namely empathy, definition, ideation, prototype, and testing. Data collection was carried out through observation, interviews, and questionnaires involving 30 respondents. The interface usability evaluation used the System Usability Scale (SUS). The results showed an increase in the average score from 52.4 (Marginal–Low category) for the previous design to 80.8 (Excellent category) for the new design, indicating that the new UI/UX design has met user needs by improving the quality of the PT. Ridho Makmur Sentosa website interface design.